PELATIHAN PEMBUATAN JAJANAN SEHAT PADA IBU PKK DI KEDUNGJAMBE SINGGAHAN - Idcha KR; Nikita WP; Dwi Kurnia PS (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Snacks are a type of food that is often consumed and known by the general public, including school children. The Food and Drug Monitoring Agency (BPOM) noted that 14.7% of snacks in the school environment contained hazardous materials such as borax, rhodamine B, formalin and methanyl yellow. Unhealthy snacks are caused by a lack of understanding in managing and maintaining the cleanliness and hygiene of the food to be sold. Snacks for school children whose health and hygiene are not guaranteed can potentially cause poisoning, digestive disorders and if it lasts for a long time will lead to poor nutritional status, therefore education about healthy snacks is needed and training in making healthy snacks Keywords : Healthy Snack, Nutrition, School Children